Differential response of LV sublayer twist during dobutamine stress echocardiography as a novel marker of contractile reserve after acute myocardial infarction: relationship with follow-up LVEF improvement. (22nd July 2015) - Joyce, Emer; Debonnaire, Philippe; Leong, Darryl P.; Abate, Elena; Katsanos, Spyridon; Bax, Jeroen J.; Delgado, Victoria; Ajmone Marsan, Nina
Abstract: Aims: Dobutamine stress echocardiography (DSE) is frequently performed to assess left ventricular (LV) contractile reserve in patients following myocardial infarction (STEMI). Given that resting LV sublayer twist assessment has been proposed as a marker of infarct transmurality, this study aimed to investigate whether response of LV subepicardial twist on DSE represents a novel quantitative marker of contractile reserve. Methods and results: First STEMI patients treated with primary percutaneous coronary intervention with a resting wall motion abnormality in greater than or equal to two segment(s) at 3 months who underwent full protocol DSE were included. Two-dimensional speckle-tracking was used to calculate LV subepi- and subendocardial twist—defined as the net difference (in degrees) of apical and basal rotation for each sublayer—at rest and peak-dose stages. Primary end point was a ≥5% absolute LV ejection fraction (LVEF) improvement between 3 and 6 months. In total, 61 patients (mean age 61 ± 12, 87% male) were included, of whom 48% ( n = 29) demonstrated follow-up LVEF improvement. Mean change in both LV subepicardial (ΔLVsubepi) twist (2.4 ± 3.0 vs. 0.00 ± 2.0°, P = 0.001) and LV subendocardial (ΔLVsubendo) twist (2.7 ± 4.5 vs. 0.25 ± 4.5°, P = 0.04) from rest to peak was significantly higher in LVEF improvers. ΔLVsubepi (odds ratio, OR 1.5, 95% confidence interval, CI 1.1–2.0, P = 0.007), but not ΔLVsubendo (OR 1.1, 95% CI 0.99–1.3, P = 0.07), twist was independently associated with follow-up LVEF improvement following adjustment for baseline LVEF and β-blockade. Conclusion: In post-STEMI patients with resting regional dysfunction, the response of LV subepicardial twist on DSE is associated with follow-up LV function improvement, suggesting recruitment in subepicardial function following STEMI reflects greater extent of contractile reserve.